A 2 × 2 array antenna with circular polarization and conical beam radiation. Issue 2 (2nd May 2013) - Sim, C. Y. D.; Han, T. Y.; Chi, C. J.; Chen, B. Y.
ABSTRACT A circular disk patch antenna loaded with a hemi‐circular slot is initially proposed for achieving circular polarization (CP). To exhibit broad CP bandwidth that can cover the WLAN 2.4 GHz operating band, the patch antenna is fed by an L‐shaped probe. To further attain conical beam radiation with peak gain of ∼8 dBic at ±30 degrees theta angle (θ), a 2 × 2 array type is proposed in this study, in which four circular disk patch array elements are arranged in a sequentially rotated fashion via a corporate feed network. Here, desirable 3‐dB axial ratio (AR) bandwidth and 10‐dB impedance bandwidth of ∼5% and 21% were measured. © 2013 Wiley Periodicals, Inc. Int J RF and Microwave CAE 24:223–228, 2014.